2014
DOI: 10.4067/s0717-95022014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Version of Femoral Neck: A Cadaveric Dried Bone Study

Abstract: SUMMARY:The aim of this study was to measure the version of femoral neck on dried Thai human femora. The version of femoral neck varies widely. It is important to know the version of femoral neck in a particular population to undertake successful femoral neck reconstructive surgery. Paired 216 dried femora of adult Thais from the bone collection maintained in the Department of Anatomy at the Faculty of Medicine, Khon Kaen University, Thailand, were used to measure the version of femoral neck. The mean+SD femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…1,13 Kimaporn et al (2005) have obtained a value of 15.5 in Thai population. 21 Jain et al and Maheshwari et al 9,10 have done a study in North Indian population and they found a value of 8.4 and 10.6 respectively. Srimathi et al (2012) have obtained a value of 9.8 in South Indian population.…”
Section: Discussionmentioning
confidence: 96%
“…1,13 Kimaporn et al (2005) have obtained a value of 15.5 in Thai population. 21 Jain et al and Maheshwari et al 9,10 have done a study in North Indian population and they found a value of 8.4 and 10.6 respectively. Srimathi et al (2012) have obtained a value of 9.8 in South Indian population.…”
Section: Discussionmentioning
confidence: 96%